Relationship between Initial CT Value, Inflammatory Markers, and Onset of Clinical Symptoms with Outcomes of Treatment Outcomes of COVID-19 Patients at Dr. M. Djamil General Hospital Padang - Irvan Medison; Chicy Widya Morfi; Elsesmita Elsesmita; Diana Nur Asrini; Hendris Utama Citra Wahyudin; Ahmad Junaidi; Jefri Sofian Leksana; Bobby Hasibuan; Adhika Rahman (HM Publisher, 2022)
Background: Treatment given for COVID-19 includes the provision of antiviral, anti-inflammatory, immunomodulatory, anticoagulant, and treatment of comorbidities and complications. The success of treatment in COVID-19 patients does not only depend on the drug given but is also influenced by clinical manifestations, clinical phase, and the presence or absence of complications and comorbidities. This study aims to assess the relationship between initial CT values, inflammatory markers, and symptom onset on treatment outcomes for COVID-19 patients at Dr. M. Djamil General Hospital Padang. Methods: This study is an observational analytic study with a retrospective cohort approach in confirmed COVID-19 patients treated at Dr. M. Djamil General Hospital Padang between 1st January – and 31st May 2021. The sample is the population that meets the inclusion criteria; confirmed COVID-19 from the results of RT PCR/TCM SARS-CoV-2, aged > 18 years, including the clinical degree of moderate, severe, critical illness. Exclusion criteria were patients with incomplete medical record data. Univariate analysis is intended to describe each research variable so that the distribution and percentage of each variable are presented in tabular form. Bivariate analysis using Chi-Square statistical test to see the relationship between variables. Results: COVID-19 patients being treated at Dr. M. Djamil General Hospital Padang were mostly in the age group above 50 years, namely 59.6%, and the female sex was treated more than the male, namely 55.5%. The moderate clinical grade is the highest proportion of hospitalized patients, namely 64.3%, followed by critical clinical 30.0% and severe clinical 5.6%. There is no relationship between the initial CT value and the outcome of COVID-19 patients. There is a relationship between IL-6 levels (initial) with the outcome of Covid-19 patients at Dr. M. Djamil General Hospital Padang. There is no relationship between the onset of clinical symptoms and the outcome of Covid-19 patients at Dr. M. Djamil General Hospital Padang. Conclusion: There is a relationship between IL-6 levels (initial) with patient outcomes, need for oxygen therapy, ferritin levels with the incidence of sepsis, initial albumin levels with initial D-Dimer levels, and IL-6 levels with D-dimers in COVID-19 patients at Dr. M. Djamil General Hospital Padang.